2019
DOI: 10.2337/db19-0086
|View full text |Cite
|
Sign up to set email alerts
|

RILP Restricts Insulin Secretion Through Mediating Lysosomal Degradation of Proinsulin

Abstract: Author Contributions. Y.Zho. conducted most of the experiments and analyzed the results. Z.L. and S.Z. conducted the animal experiments. R.Z., H.L., X.L., X.Q., and Y.Zhe. provided technical support. M.Z. carried out work on Rab26-RILP interaction. L.L. provided technical support for the pancreas sectioning. W.H. was involved with the ideas and writing the paper. T.W. conceived the idea for the project, designed the experiments, and wrote the paper. T.W. is the guarantor of this work and, as such, had full acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 58 publications
1
31
0
Order By: Relevance
“…We believe that the overexpression experiments suggest a mechanism whereby an increase in Stmn2 in the alpha cell inhibits glucagon secretion by targeting glucagon secretory granules for degradation in the endosome-lysosome pathway, perhaps in a manner similar to that of insulin secretory granules in Type 2 diabetes (52). Very recently, it has been shown that insulin secretion can be inhibited by the targeting of proinsulin for lysosomal degradation by Rab7-interacting lysosomal protein (RILP) (53). The proposed mechanism of action was through interactions between RILP and an insulin secretory granule membrane protein, Rab26.…”
Section: Discussionmentioning
confidence: 98%
“…We believe that the overexpression experiments suggest a mechanism whereby an increase in Stmn2 in the alpha cell inhibits glucagon secretion by targeting glucagon secretory granules for degradation in the endosome-lysosome pathway, perhaps in a manner similar to that of insulin secretory granules in Type 2 diabetes (52). Very recently, it has been shown that insulin secretion can be inhibited by the targeting of proinsulin for lysosomal degradation by Rab7-interacting lysosomal protein (RILP) (53). The proposed mechanism of action was through interactions between RILP and an insulin secretory granule membrane protein, Rab26.…”
Section: Discussionmentioning
confidence: 98%
“…These results suggest a mechanism whereby an increase in Stmn2 in the alpha cell inhibits glucagon secretion by targeting glucagon secretory granules for degradation in the endosome-lysosome pathway, perhaps in a manner similar to that of insulin secretory granules in Type 2 diabetes (39). Very recently, it has been shown that insulin secretion can be inhibited by the targeting of proinsulin for lysosomal degradation by Rab7-interacting lysosomal protein (RILP) (40). The proposed mechanism of action was through interactions between RILP and an insulin secretory granule membrane protein, Rab26.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying new pathways or networks that control glucagon granule biogenesis and trafficking may identify novel targets for the control of hyperglucagonemia in addition to yielding a greater understanding of alpha cell biology in both health and disease. There is an emerging hypothesis that glucagon secretion can be controlled by trafficking through the endosomal-lysosomal pathway, similar to insulin ( 136 ), and below, we highlight some recent studies that suggest glucagon may regulated through such an alternate trafficking pathway.…”
Section: Novel Proteins In the Regulation Of Glucagon Trafficking And Secretionmentioning
confidence: 95%